Characteristics of the stories sent by communication departments that has influence on journalists’ use and modification - Busto Salinas, Lorena (Historia y Comunicación Social, 2014)
The aim of this research is to find out if some aspects of press releases, apart from the newsworthy characteristics, have influence on whether the text is eventually published and in which way. The subject, the extension and the main characters of all press releases sent in four years by Atapuerca Foundation (Burgos, Spain) have been collected, as well as their penetration in six newspapers. It has been proved, among other things, that the most exclusive subject is the only one that has more possibilities to appear in the press and with a better relevance. However, the mention of a famous person or the extension of the press release do not have any influence on journalists.
Keywords: public relations; external communication; mass media; press release; press analysis